The Effect of Work Discipline and Compensation on Performance of Shopping Management Company Employees - Syamsulaiman Syamsulaiman; Agus Siswanto; Zunan Setiawan; Ivonne Ayesha; Nenden Hendayani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain if pay and work rules have an impact on employee performance at one of the enterprises in Indonesia. There are 50 persons in the whole population that are all study responders. This study makes use of primary data collected by distributing questionnaires to research site workers. Multiple linear regression is the data analysis method employed in this study and is carried out using the SPSS software. According to the study's findings, employee performance is influenced by work discipline more so than by compensation. Employee performance is concurrently impacted by pay and workplace rules.